Meaningful miracles: Unraveling eucatastrophe in the select fantasy fiction of J.K. Rowling - Swathi Metla; Yu. V. Sudha Devi (RUDN Journal of Studies in Literature and Journalism)
The Harry Potter series is the story of Harry, an orphan-hero, who is on the quest of self-discovery; it unfolds through a series of adventures he goes on with his friends at Hogwarts. The series falls into a fuzzy set - a blend of genres - Bildungsroman, fantasy tale, mystery thriller, crossover tale, children’s literature, gothic tale, and quest romance. Harry’s journey of growing up is narrated with thrilling rigour and crafted with care by J.K. Rowling; the novels are imbued with warmth, inclusivity and fun. This led to her fame, recognition and success. These novels culminate in good triumphing over evil which is a trademark of high fantasy. This phenomenon is called “poetic justice” - a term coined by Thomas Rhymer. The paper attempts to locate and analyse the Eucatastrophe which is defined by JRR Tolkien as “the sudden joyous “turn” …a sudden and miraculous grace: never to be counted on to recur”. Several instances of Eucatastrophes from the seven novels are chosen and decoded to be studied in line with how they facilitate making certain events believable or how the story evolves; they add hope, tension and often edge to the narrative. Textual and thematic analyses are used in the study to articulate the observations and underpinnings.